Quality of life profiles and their associations with depressive symptoms and cognitive impairment of community-dwelling older adults in Hong Kong - Luo, Guozhi; Li, Weiping; Wu, Donghai; Wei, Xinyue; Zang, Yanpeng; Liu, Jing-Dong (Frontiers in Public Health, 2023)
Background: This study aimed to (1) explore the quality of life (QoL) profiles of older adults in Hong Kong and (2) examine their association with predictors (age, sex, body mass index, and depressive symptoms) and distal outcome (cognitive impairment) using a person-centered approach. Methods: A total number of 328 community-dwelling older adults in Hong Kong were invited to participate in this study. Data from 259 older adults were identiﬁed as valid for the primary analysis. Latent profile analysis was used to explore QoL profiles. Multinomial logistic regression using the R3STEP function in Mplus was used to explore the predictive role of age, sex, body mass index, and depressive symptoms in profile membership. The Bolck-Croon-Hagenaars approach was used to examine how the distal outcome of cognitive impairment differs as a function of QoL profiles. Results: Three QoL profiles emerged from the latent profile analysis (Low, Moderate and High QoL). It was found that depression, but not age, sex, or body mass index, significantly predicted QoL profile membership. The results of the Bolck-Croon-Hagenaars analysis revealed no significant differences in cognitive impairment across the three QoL profiles. Conclusion: This is the first study that examined the relationship between QoL, depressive symptoms and cognitive impairment of older adults using a person-centered approach. The findings provide additional information for the evidence obtained from variable-centered approach on the associations among variables abovementioned. Our additional focus on the antecedents of emergent QoL profiles also provide practical knowledge regarding timely treatment for or prevention of depressive symptoms, which we submit will be crucial for enhancing the QoL of older adults.